High Compliance with Scheduled Nimodipine Is Associated with Better Outcome in Aneurysmal Subarachnoid Hemorrhage Patients Cotreated with Heparin Infusion - Wessell, Aaron; Kole, Matthew J.; Badjatia, Neeraj; Parikh, Gunjan; Albrecht, Jennifer S.; Schreibman, David L.; Simard, J. Marc (Frontiers in Neurology, 2017)
Introduction We sought to determine whether compliance with scheduled nimodipine in subarachnoid hemorrhage patients impacted patient outcomes, with the intent of guiding future nimodipine management in patients who experience nimodipine-induced hypotension. Methods We performed a retrospective analysis of 118 consecutive aneurysmal subarachnoid hemorrhage patients treated with the Maryland Low-Dose IV Heparin Infusion Protocol. Patients were categorized into three independent nimodipine compliance groups: ≥1 dose held, ≥1 dose split, and no missed or split-doses. A split-dose was defined as 30 mg of nimodipine administered every 2 h. Our primary outcome was discharge to home. Bivariate and multivariable logistic regression analyses were used to assess predictors of discharge disposition as a function of nimodipine compliance. Results Of the 118 patients, 20 (17%) received all nimodipine doses, 6 (5%) received split-doses but never had a full dose held, and 92 (78%) had ≥1 dose held. Forty-five percent of patients were discharged to home, including 75% who received all doses, 67% who received ≥1 split-doses, and 37% with ≥1 missed doses (p = 0.003). Multivariable analysis showed that, along with age and World Federation of Neurosurgical Societies grade, nimodipine compliance was an independent predictor of clinical outcome; compared to missing one or more nimodipine doses, full dosing compliance was associated with increased odds of discharge to home (odds ratio 5.20; 95% confidence intervals 1.46–18.56). Conclusion In aneurysmal subarachnoid hemorrhage patients with modified Fisher scores 2 through 4 who are cotreated with a low-dose heparin infusion, full compliance with nimodipine dosing was associated with increased odds of discharge to home.